Analisis Proses Pembelajaran Aksara Arab Melayu pada Kelas IV di MIS YPI Batangkuis melalui Metode Kualitatif Deskriptif - Mursal Aziz; Nur Aisyah Dalimunte; Nikmah Mustika; Wilda Rahmayani Ritonga; Liza Umami (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research aims to analyze the Arabic-Malay script learning process in class V at MIS YPI Batangkuis using descriptive qualitative methods. The research method in this study was carried out using 2 (two) data collection techniques, namely interviews and observation. The objects of this research were 30 students in class IV MIS YPI Batangkuis. Data collection techniques in this research were carried out using tests and questionnaires which took place face to face with students. Data analysis methods include assessing writing test scores, calculating the percentage of reading ability, as well as evaluating overall results to understand the effectiveness of teaching Arabic-Malay. It is hoped that the findings from this research will provide a more comprehensive view of the teaching strategies that best support Arabic-Malay language learning in the fifth grade environment of MIS YPI Batangkuis. The results of this research can be a reflection to improve existing teaching methods. By understanding the successes and challenges in the learning process, more effective strategies can be developed to improve students' understanding of Arabic-Malay. It is hoped that the implications of this research can help develop better teaching guidelines and improve the quality of Arabic-Malay language education at a broader level.